Comparison of laboratory methods for diagnosis of human visceral leishmaniasis in the Center-West Region of São Paulo State, Brazil - Lívia Carla Ramos; Kethlyn Magliani de Figueiredo Reihner; Luciana da Silva Ruiz; Laís Anversa; Sâmea Fernandes Joaquim; Jose Eduardo Tolezano; Diego Borin Nóbrega; Virgínia Bodelão Richini Pereira (Acta Scientiarum. Health Sciences, 2023)
Visceral leishmaniasis (VL) is a neglected disease and represents an important public health problem. The present study aimed to compare the conventional laboratory methods with the molecular method for VL diagnosis in human blood samples. Direct parasitological test of bone marrow aspirate (direct parasitological test), rapid immunochromatographic test (RIT), indirect immunofluorescent antibody test (IFAT) and polymerase chain reaction (PCR) were used to evaluate 26 human samples with clinical suspicion of VL. The positivity rates obtained for direct parasitological test, RIT, IFAT and PCR were 80.8%, 80.8%, 73.1% and 84.6%, respectively. PCR had greater positivity and agreement with the other methodologies. Therefore, the use of PCR in the diagnostic routine should be encouraged to complement the serological results.